HARMONIZATION ARBITRATION LAW ASEAN COUNTRIES : A DISCOURSE FOR INVESTOR–STATE ARBITRATION IN THE ASEAN ECONOMIC COMMUNITY (AEC) - Suyud Margono (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
The implementation of the ASEAN Economic Community (AEC), may increase  trade and commercial activities in the number of intra-ASEAN, including investment disputes between investors and ASEAN member Countries. In that regard, the ASEAN Comprehensive Investment Agreement (ACIA) gives aggrieved investors the option to refer their disputes to arbitration in resolving their disputes.  Many  foreign arbitrage decisions is found to be time consuming when it comes to enforcing the decision and cases over the final and legal binding arbitrage decision being overturned by court’s decision in Indonesia. Thus the efficiency and effectiveness of the arbitration process is being negated. The ASEAN Comprehensive Investment Agreement (ACIA), that provides the legal  basis for the AEC’s liberalized investment regime, establishes an investor-state dispute resolution mechanism (ISDR mechanism).Keywords:  Harmonization of Arbitration Law, ASEAN Economic Community, Enforcement Arbitral Award